Perkembangan Sosio-Emosional dan Pembelajaran Tahsin IQRO Siswa Kelas 1 - AnnisaNur Hasanah; Ainun Najikha; Ela Komala (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
This study examines the socio-emotional development characteristics of first-grade elementary school students (ages 6-7 years) and its implications for tahsin Iqro learning. Early elementary school is a crucial period in forming social skills and emotional regulation that significantly impacts learning success, including Quranic reading instruction. The research objectives are to describe socio-emotional development characteristics, analyze implications for tahsin Iqro learning, and formulate appropriate learning strategies. This study employs a qualitative approach with mixed methods combining literature study and in-depth interviews with tahsin Iqro teachers of first-grade students at SDIT Wisata Hasanah Pontianak. Data were collected through in-depth interviews and literature review of scientific journals, then analyzed using Miles and Huberman’s qualitative data analysis technique. Findings show first-grade students’ socio-emotional characteristics include: need for social acceptance, high sensitivity to praise and criticism, developing emotional regulation abilities, and early self-concept formation. Implications for tahsin Iqro learning include: using enjoyable and meaningful methods, applying positive reinforcement, group learning supporting positive social interaction, and creating emotionally safe learning environments. The study recommends Islamic education teachers integrate socio-emotional development understanding in designing effective and humanistic tahsin Iqro learning strategies based on developmentally appropriate practice.